Fish Bone Derived Bi-Phasic Calcium Phosphate Coatings Fabricated by Pulsed Laser Deposition for Biomedical Applications - (:unkn) unknown (MDPI, 2020)
We report on new biomaterials with promising bone and cartilage regeneration potential, from sustainable, cheap resources of fish origin. Thin films were fabricated from fish bone-derived bi-phasic calcium phosphate targets via pulsed laser deposition with a KrF * excimer laser source (lambda = 248 nm, tau(FWHM) <= 25 ns). Targets and deposited nanostructures were characterized by SEM and XRD, as well as by Energy Dispersive X-ray (EDX) and FTIR spectroscopy. Films were next assessed in vitro by dedicated cytocompatibility and antimicrobial assays. Films were Ca-deficient and contained a significant fraction of beta-tricalcium phosphate apart from hydroxyapatite, which could contribute to an increased solubility and an improved biocompatibility for bone regeneration applications. The deposited structures were biocompatible as confirmed by the lack of cytotoxicity on human gingival fibroblast cells, making them promising for fast osseointegration implants. Pulsed laser deposition (PLD) coatings inhibited the microbial adhesion and/or the subsequent biofilm development. A persistent protection against bacterial colonization (Escherichia coli) was demonstrated for at least 72 h, probably due to the release of the native trace elements (i.e., Na, Mg, Si, and/or S) from fish bones. Progress is therefore expected in the realm of multifunctional thin film biomaterials, combining antimicrobial, anti-inflammatory, and regenerative properties for advanced implant coatings and nosocomial infections prevention applications.
Keywords: antimicrobial coatings; advanced implants; nosocomial infections prevention; cytocompatibility; sustainable resources; PLD; HYDROXYAPATITE THIN-FILMS; GLASS-CERAMIC COATINGS; NANO-HYDROXYAPATITE; SUBSTITUTED HYDROXYAPATITES; PHYSICOCHEMICAL PROPERTIES; BIOCERAMICS; TEMPERATURE; COMPOSITE; BEHAVIOR; IMPLANT